Analyzing the Influence of Price, Promotion, and Trust on Consumer Purchase Decisions: A Study of Mr. Frozen Food on the Shopee Marketplace - Fedianty Augustinah; Ambarwati Octaviani; Dian Ferriswara; Andry Herawati; Liling Listyawati (Universitas Yudharta Pasuruan, 2024)
AbstractThis research investigates the impact of price, promotion, and trust on consumer purchasing decisions for Mr. Frozen Food through the Shopee platform. Applying a quantitative approach with a sample of 100 respondents, the study reveals that both price and trust significantly and positively influence purchasing decisions, while promotion has a significant negative effect. The regression analysis shows that all three variables collectively influence purchasing decisions, with an adjusted R square of 98.8%. These results highlight that competitive pricing and consumer trust are key drivers of purchasing behavior, whereas promotional strategies may require reassessment. The study offers valuable insights for shaping marketing strategies within the e-commerce sector. AbstrakStudi ini meneliti dampak harga, promosi, dan kepercayaan terhadap keputusan pembelian konsumen Mr. Frozen Food di platform Shopee. Dengan pendekatan kuantitatif yang melibatkan 100 partisipan, penelitian ini menemukan bahwa harga dan kepercayaan konsumen memiliki pengaruh positif signifikan terhadap keputusan pembelian, sementara promosi berdampak negatif signifikan. Hasil analisis regresi menunjukkan bahwa ketiga variabel tersebut secara simultan memengaruhi keputusan pembelian, dengan nilai adjusted R square sebesar 98,8%. Temuan ini menegaskan pentingnya harga yang kompetitif dan kepercayaan dalam meningkatkan keputusan pembelian konsumen, sementara efektivitas promosi memerlukan evaluasi lebih lanjut. Penelitian ini memberikan kontribusi bagi pengembangan strategi pemasaran di industri e-commerce.